HUBUNGAN PENGETAHUAN GIZI DENGAN KONSUMSI KFC MAHASISWA PENDIDIKAN TATA BOGA UNIVERSITAS NEGERI PADANG - Lindra, Maifo; Fridayati, Lucy; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2016)
This study was aimed to describe nutrition a knowledge and KFC consumption and analyze the relation between nutrition a knowledge with KFC consumption Students Culinary Education UNP. This study was a correlational, with a population in this research was 151 people, and all of them sample. The data were collection techniques for nutrition a knowledge by using a questionnaire enclosed in the form multiple choise as well as KFC consumption by using open questionnaire in the form essays. The results showed the nutrition a knowledge of students included in either category is good (54.97%). At KFC consumption variables known that the types of products most in demand is the fried chicken (27.5%) with frequencies belonging to the low level (1-2 time a week) (81.5%), and is often consumed on special days (14.5%). The location is eating visited Basko Grandmall (35%). The reason students consuming KFC because of good (23.6%). Correlation test results showed that there is a positive and significant relation between nutrition a knowledge with KFC consumption by thitung 7.036 at the level 0.000 Sig. Contributions nutrition a knowledge on KFC consumption students culinary education UNP is 24,9%.Keyword: Nutrition Knowledge, KFC Consumption